Experience Skype to the max : the essential guide to the world's leading internet communications platform - Courtney, Jim (Technology in action series., 2015)
"[This] shows you how to make the most of Skype's full range of features on any device. Discover tips and tricks for saving time, saving money, and fostering better communication at work or in your personal projects. Go beyond simple voice calling and discover Skype as a multimedia cross-platform collaboration tool, wherever you are in the world. Learn how to connect to Skype from your devices whether in the home office, on the road, roaming on your mobile or over WiFi, and understand the security and privacy requirements in each case. Discover the best ways to call or message landlines and mobile phones at minimum cost, and how to manage your account and payments, depending on your needs ... As work and home lives become increasingly intertwined, this book is your essential guide to building and sustaining your important relationships on one reliable platform ... Written with business employees and consumers in mind, Experience Skype to the Max is a guide to real-time social networking for building and sustaining everyday business and personal relationships, whether geographically dispersed business teams, road warriors, special interest groups, friends and family, the wanderlust world traveler or anyone else who wants to get more out of their Skype experiences"--Publisher's description.